Results from a clinical trial evaluating the efficacy of real-time body surface visual feedback in reducing patient motion during lung cancer radiotherapy. (1st February 2018) - Price, Gareth J.; Faivre-Finn, Corinne; Stratford, Julia; Chauhan, Sheena; Bewley, Michelle; Clarke, Laura; Johnson, Corinne N.; Moore, Christopher J.
Abstract: Introduction: Optical surface measurement devices are a maturing technology in radiotherapy. The challenge for such devices is to demonstrate how they can improve clinical care. We present results from a phase 1 clinical trial designed to test the hypothesis that if presented with live data from a novel optical measurement device, showing their deviation from an ideal radiotherapy treatment position, patients will be able to better control their motion and increase their geometrical conformance. Method and materials: Fourteen lung cancer patients were enrolled in a prospective clinical study and asked to use a variety of visual feedback schema from a novel in-house developed optical surface measurement device. The magnitude and regularity of their body surface motion using the different schema was compared to that when free-breathing at three time-points throughout their radiotherapy treatment schedule. Additionally, 4D Cone Beam CT data, acquired simultaneously with the optical measurements, was used to test if improvements in external motion are reflected in changes in internal tumor motion. Results: The primary endpoint of the trial, device tolerability assessed by the fraction of participants completing all study sessions, was 86%. Secondary endpoints showed that use of the visual feedback device was found to statistically significantly decrease body surface motion magnitude by an average of 17% over the study cohort, although not universally. Similarly body surface motion variability was decreased by 18% on average. Internal tumor motion magnitude was also found to be statistically significantly decreased by an average of 14% when using the feedback device. Reduction in external motion was predictive of reduced internal motion but no evidence of a simple correlation between changes in internal and external motion magnitude was found. Conclusions: Visual feedback of live motion is well tolerated by lung cancer patients and can reduce both body surface and tumor motion.